Use of ICS in COPD: From Blockbuster Medicine to Precision Medicine. (2nd November 2017) - Contoli, Marco; Corsico, Angelo G.; Santus, Pierachille; Di Marco, Fabiano; Braido, Fulvio; Rogliani, Paola; Calzetta, Luigi; Scichilone, Nicola
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is a major cause of mortality worldwide, whose burden is expected to increase in the next decades, because of numerous risk factors, including the aging of the population. COPD is both preventable and treatable by an effective management including risk factor reduction, prevention, assessment, and treatment of acute exacerbations and co-morbidities. The available agents approved for COPD treatment are long-acting or ultra-long-acting β2-agonists (LABAs) and long-acting muscarinic antagonists (LAMAs) bronchodilators, as well as inhaled corticosteroids (ICS) in combination with LABAs. ICS use has been restricted only to selected COPD patients by the most recent documents, mainly based on the risk of exacerbations. However, several observational studies showed a high rate of prescription of ICS in COPD, irrespective of clinical recommendations, questioning the efficacy of these compounds in unselected patients with COPD and leading to possible increase risk of side effects related to ICS use. After examining the low levels of adherence in primary care and in the clinical settings to national and international recommendations for the treatment of COPD in different countries, the most common drivers of the prevailing use of ICS are critically reviewed here by examining their pros and cons, aimed at identifying evidence-based drivers for a proper selection of patients who may benefit from the proper use of ICS.